Power BI masterclass (Packt Publishing, 2021)
Master Microsoft Power BI and learn to perform Power BI Calculation Groups, Power BI Charticulator, Power BI Performance Tips, Power BI AI, DAX table calculations, and Excel. Microsoft Power BI is an advanced yet easy-to-get-started self-service business analytics/business intelligence solution. Power BI is also a great tool for data science. A lot of data scientists like to use it for visualizing and presenting the findings. Therefore, learning to use this tool can be a valuable skill for data science jobs. This course is divided into six sections. We will first start with understanding DAX table calculations with Power BI Desktop and Excel and master DAX. In the second section, we will learn Microsoft Power BI tips and tricks from project experience and research. In the third section, we will be solving data prep challenges. In the fourth section, we will master advanced DAX calculations and build on your acquired knowledge from the prior sections. In section five, we will be combining data science tools such as Python with Power BI. In the last section, we will cover Power BI best practices, Power BI Calculation Groups, Power BI Charticulator, Power BI performance tips, and Power BI AI. By the end of this course, you will have the skills and capabilities to analyze and understand data with Power BI.